2023
DOI: 10.3889/oamjms.2023.9513
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Mercury Emissions in Soot with the Quadrant Method on Combustion of Gold in Aceh Jaya District

Abstract: BACKGROUND: Gold mining, especially by the community, causes many problems. One of the problems is the increase in mercury pollution. The amalgamation technique involving mercury in the gold processing process is still widely used by miners and has the potential to threaten the health of workers and the surrounding community. AIM: This study aimed to identify mercury levels in soot at the location of a traditional gold processing plant in Paya Seumantok Village, Krueng Sabee District, Aceh Jaya District. METHO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
0
0
0
Order By: Relevance
“…Children with test sample code 3 are declared to have the highest mercury identification based on the analysis results (62.20). The results of this study showed that all urine samples taken contained mercury, as many as eight urine samples contained mercury above the threshold set by Human Biomonitoring (HBM), 7 μg/L (Lensoni, et al, 2023), while three In the urine sample there is a mercury content below a predetermined threshold. This shows that as many as 88% of stunting toddlers contain mercury in the urine while 12% contain mercury below a predetermined threshold.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…Children with test sample code 3 are declared to have the highest mercury identification based on the analysis results (62.20). The results of this study showed that all urine samples taken contained mercury, as many as eight urine samples contained mercury above the threshold set by Human Biomonitoring (HBM), 7 μg/L (Lensoni, et al, 2023), while three In the urine sample there is a mercury content below a predetermined threshold. This shows that as many as 88% of stunting toddlers contain mercury in the urine while 12% contain mercury below a predetermined threshold.…”
Section: Resultsmentioning
confidence: 80%
“…The highest concentration of mercury in Gampong Paya Seumantok is due to the large number of artisanal gold processing industries in the area. Lensoni (2023) reported concentrations in the urine of the Seumantok Gampong Paya community. Sixteen of 91 urine samples did not show mercury, while the remaining 75 samples were found to contain mercury.…”
Section: Resultsmentioning
confidence: 99%